SPOP Inhibition of Endometrial Carcinoma and Its Clinicopathological Relationship - Qing Zhu; Guanghui Zhang; Mingyang Tang; Rumin Zheng; Huaiyong Gan (Applied Bionics and Biomechanics)
Objective. Endometrial carcinoma (EC) ranks first in the incidence of female genital malignancies in developed countries. SPOP (speckle-type POZ protein) has changed in EC with a statistically high frequency. This research may play a crucial role in the initiation and progression of EC, ultimately leading to fresh therapeutic targets. Explore the expression of SPOP in EC; observe its effect on the proliferation, invasion, and migration of EC cells after upregulating the expression of SPOP through RNA activation. Methods. The expression levels of SPOP protein in 150 EC tissues and 45 normal endometrial tissues were detected by immunohistochemistry and Western blotting. Analyze the relationship between SPOP expression and clinicopathological characteristics. The differences of the proliferation, migration, and invasion abilities between before and after transfection were analyzed using CCK-8 and Transwell assays. Results. The results of immunohistochemistry and Western blotting showed the expression level of SPOP in EC tissue significantly reduced or even missed compared with normal endometrial tissue. The results of CCK-8 showed that the growth of EC significantly slowed down after the upregulating of SPOP expression. The results of the Transwell assay showed the migration and invasion abilities of EC cells were weakened after the level of SPOP was upregulated. Conclusions. The expression level of SPOP in EC tissues is lower and related to the clinicopathological features compared with normal endometrial tissues. After upregulating the SPOP expression by RNA activation in EC cell lines, the abilities of proliferation, migration, and invasion of cells were significantly inhibited.